Firm focus, market orientation and firm performance within the health insurance industry / Mohammed Majeed, Kwabena Ekremet and Setsoafia-Tukpeyi Godwin - Majeed, Mohammed; Ekremet, Kwabena; Godwin, Setsoafia-Tukpeyi (Accounting Research Institute (ARI), 2022)
Marketing orientation of businesses has become a strategy and priority for service providers in building strong value for customers by predicting and adapting to competitor innovations and services. This study looked at firm focus, firm performance and the three dimensions of market orientation using 168 respondents from the private health insurance industry. The study found that firms paying critical attention to the exclusive needs of their customers and competitor services remain stronger in the market. The study revealed that in order to improve long-term outlook, health insurance firms are required to implement the requisite market orientation dimensions to increase the success of firm performance.